Societies, Boards, Etc., on Which the Institute is Represented (c0a7f940-96c3-45de-b999-19c460605a7e) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
Following is the personnel of the various society and national committees on which the A I M E is officially represented United Engineering Society Officers of the Board, 1921 JOHN VIPOND DAVIES, President CALVERT TOWNLEY, 1st Vice-president ALFRED D FLINN, Secretary WILLIAM L SAUNDERS, 2d Vice-president JOSEPH STRUTHERS, Treasurer Finance Committee House Committee CALVERT TOWNLEY, Chairman ALFRED D FLINN, Chairman GEORGE H PEGRAM . H S CROCKER WILLIAM L SAUNDERS BRADLEY STOUGHTON GEORGE M BASFORD CALVIN W RICE F L HUTCHINSON